Students’ Factors Affecting Undergraduates’ Perceptions of their Teaching and Learning Process within ECTS Experience - De La Fuente, Jesus; Cardelle-Elawar, Maria; Peralta, Francisco J.; Sánchez, Maria D.; Martínez, Jose M.; Zapata, Lucia (Frontiers in Psychology, 2011)
Introduction. The objective of this research was to learn what variables determine satisfaction with the teaching-learning process (TLP), from the perspective of students participating in the ECTS experience (European Credit Transfer System). Method. A total of 1490 students from the Universities of Almería and Granada (Spain) participated in an evaluation of their class subjects. They completed a protocol for evaluating the ECTS experience. Analyses of Variance were carried out, taking different measures as independent variables, such as student’s grade average, year in school, branch of studies, workload in terms of ECTS credits per subject and the use of e-learning. Perception of TLP was used as the dependent variable. Results. Variables that establish significant differences in the perception of the TL process were determined. Student’s grade average (in favor of high performers), year in school (in favor of earlier years), ECTS load (in favor of subjects with a medium load of credits), and e-learning (in favor of its use) establish a sufficiently delimited profile of factors that trigger a favorable perception of this process. Discussion and Conclusions. The appearance of significant differences showed that perception of TLP depends on different variables that were assessed. Thus, it is important to take these variables into consideration in giving shape to the European Higher Education Area. We comment on the results and their implications for the large-scale implementation of the ECTS.